Infrared and EPR spectroscopic study of open-shell reactive intermediates: F + NH₃ in solid argon - Misochko, Eugenii Ya.; Goldschleger, Ilya U.; Akimov, Alexander V.; Wight, Charles A. (Физика низких температур, 2000)
Mobile F atoms react with NH₃ molecules in an argon matrix at temperatures T=7–35 K. The open-shell NH₂–HF complex was observed by EPR and infrared spectroscopies as the main product of this reaction. The hyperfine constants of the NH₂–HF complex aN=1.20 mT, aH=2.40 mT, and aF=0.70 mT were determined from the EPR spectra of samples using NH₃, ¹⁵NH₃ and ND₃ isotopomers. Prominent features of the infrared spectrum of NH₂–HF are a strongly red-shifted HF stretching mode (Δv≈−720 cm−1(Δv≈−720 cm⁻¹ relative to that for isolated HF) and strong absorptions at 791 and 798 cm−1798 cm⁻¹ attributed to HF librational modes in the complex. Quantum chemistry calculations reveal that the hydrogen-bonded NH₂–HF complex has a planar C₂v structure and a binding energy of 51 kJ/mol. Calculated hyperfine constants and vibrational frequencies of the complex are in good agreement with those observed in the EPR and IR experiments.